Pancreaticopleural fistula causing recurrent pleural effusion in acute pancreatitis - Vipul Chechani; Himanshu Tadvi; Umesh Bhimani (Wolters Kluwer Medknow Publications, 2022)
Digestive property intrinsic to pancreatic secretions can cut through the fascial planes and may form a pancreaticopleural fistula which is an extremely rare critical complication of pancreatitis in children. It links the pancreas with the pleural cavity through the diaphragmatic hiatus which can feed the pleural space with amylase-rich secretions and can cause recurrent pleural effusion. We report a rare case of gross left-sided pleural effusion (hemothorax) in a patient due to pancreatic etiology. The clinical presentation was deceptive since the patient presented with predominantly respiratory complaints. Many patients go through extensive pulmonary evaluation before the pancreas is recognized as the site of basic pathology. Pleural fluid amylase levels and visualizing the fistula tract from the pancreatic duct to the pleural space by radiological imaging provide the confirmation of this complication. High index of suspicion of pancreatic etiology in recurrent massive hemorrhagic pleural effusion may lead to prompt diagnosis.